West Bank and Gaza : economic performance, prospects, and policies : achieving prosperity and confronting demographic challenges - International Monetary Fund.; Valdivieso, Rosa. (Washington, D.C. : International Monetary Fund, 2001)
This is the latest in a series of economic reports by staff economists in the IMF's Middle Eastern Department. This book discusses the latest economic data coming out of the West Bank and Gaza Strip, with a particular emphasis on growing demographic concerns. The work is enhanced by the addition of numerous data tables and graphs, which extensively analyze economic trends in the region.
Includes bibliographical references: p. 129-134.
osa 27/09/2016, gau 02/11/2016
Loans
Keywords: Economic conditions; Economic policy; West Bank; Gaza Strip